2017
DOI: 10.1038/s41598-017-02546-x
|View full text |Cite
|
Sign up to set email alerts
|

Colonic infusions of short-chain fatty acid mixtures promote energy metabolism in overweight/obese men: a randomized crossover trial

Abstract: Short-chain fatty acids (SCFA), formed by microbial fermentation, are believed to be involved in the aetiology of obesity and diabetes. This study investigated the effects of colonic administration of physiologically relevant SCFA mixtures on human substrate and energy metabolism. In this randomized, double-blind, crossover study, twelve normoglycaemic men (BMI 25–35 kg/m2) underwent four investigational days, during which SCFA mixtures (200 mmol/L) high in either acetate (HA), propionate (HP), butyrate (HB) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
225
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 245 publications
(248 citation statements)
references
References 52 publications
11
225
0
1
Order By: Relevance
“…Although fasting IL-1b was significantly decreased by the high acetate mixture compared with the high propionate mixture, there was no significant difference compared with placebo or in IL-1b postprandially between treatments (54). Furthermore, changes in other proinflammatory cytokines (TNF-a, IL-6, and IL-8) did not significantly differ between treatments in either the fasting or postprandial conditions (54). The study by van der Beek et al (55) reported lower fasting plasma TNF-a concentrations after distal administration of acetate compared with placebo, however this did not reach significance.…”
Section: Effect Of Scfas On Systemic Inflammationmentioning
confidence: 61%
See 3 more Smart Citations
“…Although fasting IL-1b was significantly decreased by the high acetate mixture compared with the high propionate mixture, there was no significant difference compared with placebo or in IL-1b postprandially between treatments (54). Furthermore, changes in other proinflammatory cytokines (TNF-a, IL-6, and IL-8) did not significantly differ between treatments in either the fasting or postprandial conditions (54). The study by van der Beek et al (55) reported lower fasting plasma TNF-a concentrations after distal administration of acetate compared with placebo, however this did not reach significance.…”
Section: Effect Of Scfas On Systemic Inflammationmentioning
confidence: 61%
“…Acetate is the primary SCFA to enter circulation, and thus has the most potential to exert systemic anti-inflammatory effects (96). In contrast, butyrate is primarily absorbed by colonocytes (96), which may explain why there were no significant changes in inflammation in studies that used butyrate (27,28,54).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This in vivo data confirm the in vitro stimulation of PYY and GLP-1 from a colonic cell line by butyrate and propionate 166 . Colonic infusions of SCFA mixtures, in concentrations and ratios similar to the ones reached after fiber intake, increased fat oxidation, energy expenditure and PYY, and decreased lipolysis in overweight/obese men 172 . The systemic availability and metabolism of colonic-derived SCFAs in healthy subjects has been demonstrated using stable isotopes.…”
Section: Introductionmentioning
confidence: 66%